Engineering heterogeneity of precision nanoparticles for biomedical delivery and therapy. Issue 6 (11th May 2021) - Zheng, Di; Yang, Kuikun; Nie, Zhihong
Abstract: Nanoparticle (NP)‐based vehicles are attractive for biomedical delivery and therapy, owing to improved therapeutic efficiency and reduced adverse effects compared to free drugs. Uncontrolled NP heterogeneity at the suspension level or single particle level poses grand challenges in the effective use of NPs for biology and medicines. Precision nanoparticles (PNPs) are a class of discrete nanostructures exhibiting elaborately tailored surface or structural heterogeneity, but minimal variations between nanostructures in one solution. Benefiting from their precisely controlled NP heterogeneity, PNPs have emerged as promising platforms for modulating various biological processes to improve the biomedical performance of NP‐based vehicles. This review summarizes recent advances in the development of precisely tailored PNPs for biomedical applications, with an emphasis on the nano‐bio interactions, and drug delivery and therapy. We start with a brief overview of the major categories of PNPs and their fabrication strategies (section 2). We then focus on reviewing the use of PNPs for enhancing biomolecular recognition or detection, regulating the NP‐protein interactions, modulating the NP‐biomembrane interactions, and improving the biological delivery and therapy (section 3). Finally, we discuss the challenges and perspectives on the design and use of PNPs for biomedical applications (section 4). Abstract : Precision nanoparticles (PNPs) are a class of discrete nanostructures with elaborately tailored surface or structural heterogeneity, but minimal variations between nanostructures in one solution. We review recent advances in the design and development of precisely tailored PNPs for biomedical applications, with an emphasis on the biomolecular recognition, nano‐bio interactions, and drug delivery and therapy.